DAMPAK PERILAKU NORMA SOSIAL TIDAK BIASA TERHADAP KUALITAS LAYANAN SELAMA MASA PANDEMI COVID-19 - Fitriany, Rifda; Purwanto (MANAJEMEN DEWANTARA, 2024)
Unusual social norm behavior or what is referred to as new habits has an impact on the process of service interaction during the Covid-19 pandemic. Service providers face a dilemma between implementing health protocols with the consequence of reducing service quality dimensions or the behavior of continuing to ignore health protocols with the consequence of a massive virus transmission process. The pandemic period destroys all unusual service interactions, leading to changes in service models and having an impact on customer satisfaction.    The purpose of the preset study was to examine the effects of social norms on intimacy, competence, disgust and humanness as well as customer satisfaction on retail service interactions during the Covid-19 pandemic. A sample of 257 respondents was analyzed using AMOS 22.0.    Results of the analysis show that, first, unusual social norm had an effect on the intimacy of waiters with customers. Second, unusual social norms had an effect on waiters’ competence. Third, unusual social norms had an effect on disgust in service interactions. Fourth, unusual social norms had an effect on humanness in service interactions. Finally, intimacy, competence, disgust and humanness had an effect on customer satisfaction.